FWI Performance Improvement with the Use of Wavelet Transforms - Malvar, Sara; Dolci, Daiane I.; Carmo, Bruno Souza (Digital Subsurface Conference in Latin America, 2021)
In this work, we use wavelet transforms and compression to improve FWI overall efficiency.